EDUKASI CUCI TANGAN DAN SIKAT GIGI YANG BAIK DAN BENAR PADA SISWA SD, SMP, DAN SMK DI SD WONOSARI 2 SEMARANG - Kuspranoto, Abdul Haris; Hadi, Syaikhul; Mugiyanto; Walida Zakiyani, Khilya; Zahrotul Himmah, Nila Ulya (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2025)
A clean and healthy lifestyle is vital in maintaining health, especially for school-age children. For example, washing hands regularly with soap can help prevent the spread of germs and diseases. Likewise, brushing your teeth properly at least twice daily can reduce the risk of dental and oral health problems such as cavities or gingivitis. The community service activities carried out aim to provide understanding and skills to students at elementary and secondary education levels in terms of washing their hands and brushing their teeth properly. For example, through interactive lectures, students can learn directly how to properly wash their hands. In addition, with demonstrations and direct practice, students can directly try the correct steps themselves. At SD Wonosari 2 Semarang, this activity was attended by 147 participants from various levels of education, such as SD Wonosari 2, SMP Negeri 28, and SMK Bina Nusantara. With the pretest-posttest evaluation method, the results showed that there was a significant increase in students' understanding and practice after participating in this educational activity. This shows how important education about a clean and healthy lifestyle is for the younger generation to prevent infectious diseases and maintain overall health.